الجذور التاريخية لأزمة مياه نهر النيل حتى المبادرة المصرية لعام 1999 - ذنون, مصعب عطية (lark, 2018)
The end of the nineteenth century had witnessed the beginning of water agreements about the Nile river when most of the Nile Basin countries were under foreign domination. Most of these agreements were aimed at the colonial countries for the purpose of achieving their interests, which lasted more than half a century. After these countries had got their independence, they refused these agreements. As a result of these developments, the issue of the Nile waters has become a major concern at the official, academic and media levels. The Ethiopian demands in the waters of the Nile have been central to this crisis for many reasons, foremost of which is that Ethiopia is the most important country in terms of its contribution to the Nile River, which contributes about 80% of the Nile water revenues. Therefore, the researcher dealt with the crisis of the Nile water during the period (1891-1999), which began with the protocol of 1891 and ended at the initiative of 1999, using the historical approach and the analytical method to cause the crisis.